Pseudomeningocele Aspiration and Blood Patch Effectively Treats Positional Headache Associated With Postoperative Lumbosacral Pseudomeningocele. Issue 15 (1st August 2017) - Sandwell, Stephen; Walter, Kevin; Westesson, Per-Lennart
Abstract : Study Design: Retrospective chart review with limited prospective follow-up survey. Objective: To evaluate the efficacy and safety of blood patch injection for the treatment of positional headaches caused by postoperative lumbosacral pseudomeningoceles. Summary of Background Data: Pseudomeningocele is one of the most common complications after posterior lumbosacral spinal surgery. Common treatments include bedrest, abdominal binder use, subarachnoid lumbar drainage, and surgical re-exploration for durotomy closure. To date, only small case reports support the use of epidural blood patch injection for symptomatic pseudomeningocele treatment. Methods: A retrospective chart review analyzed the outcomes and complications of 19 consecutive patients who underwent blood patch injection, with and without pseudomeningocele aspiration, for symptomatic postoperative lumbosacral pseudomeningoceles between 2009 and 2015. An attempt was made to survey patients by phone regarding satisfaction. Results: As of last follow-up (average time = 22.3 months), 16 patients (84%) experienced headache resolution after blood patch injection and did not require further treatment of their pseudomeningocele. In addition to symptomatic improvement, 12 of the 16 successful patients had imaging, which demonstrated pseudomeningocele resolution. Persistent pseudomeningoceles were demonstrated on imaging among all three unsuccessful patients. Conclusion: Pseudomeningocele aspiration followed by blood patch is an effective treatment for symptomatic postoperative lumbosacral pseudomenigocele. This is a minimally invasive alternative to surgical re-exploration with durotomy closure. Injections are most effective when performed early after pseudomeningocele development. Level of Evidence: 4